Improved cytocompatibility and antibacterial properties of zinc-substituted brushite bone cement based on β-tricalcium phosphate - Fadeeva, Inna V.; Goldberg, Margarita A.; Preobrazhensky, Ilya I.; Mamin, Georgy V.; Davidova, Galina A.; Agafonova, Nadezhda V.; Fosca, Marco; Russo, Fabrizio; Barinov, Sergey M.; Cavalu, Simona; Rau, Julietta V. (Journal of materials science. Materials in medicine, 2021)
For bone replacement materials, osteoconductive, osteoinductive, and osteogenic properties are desired. The bacterial resistance and the need for new antibacterial strategies stand among the most challenging tasks of the modern medicine. In this work, brushite cements based on powders of Zinc (Zn) (1.4 wt%) substituted tricalcium phosphate (β-TCP) and non-substituted β-TCP were prepared and investigated. Their initial and final phase composition, time of setting, morphology, pH evolution, and compressive strength are reported. After soaking for 60 days in physiological solution, the cements transformed into a mixture of brushite and hydroxyapatite. Antibacterial activity of the cements against Enterococcus faecium, Escherichia coli , and Pseudomonas aeruginosa bacteria strains was attested. The absence of cytotoxicity of cements was proved for murine fibroblast NCTC L929 cells. Moreover, the cell viability on the β-TCP cement containing Zn 2+ ions was 10% higher compared to the β-TCP cement without zinc. The developed cements are perspective for applications in orthopedics and traumatology.